The semantic space of the personality of adult active web-users - Medvedskaya, Elena Ivanovna; Onufriieva, Liana Anatoliivna; Tavrovetska, Natalia Ivanivna (Insight: the psychological dimensions of society, 2020)
A common problem of the impact of online practiceson the cognitive sphere of adult consumers of informationis discussed in the article. The purposeof the article is to test the hypothesis on a greater cognitive complexity of consciousness of activeweb-users in the field of knowledge about the personality,as they more often have access to an unlimitedamount of network information, in particularin the sphere of social perception. Methods. Theresearch was carried out on a homogeneous sampleof respondents by the age (all participants were olderthan 35 years old) and by the sphere of professionalactivity (higher education, representatives of intellectualwork). Based on an anonymous questionnairefrom a total sample, two groups were differentiatedbased on the personal preferences of the media (traditional,paper, and digital). Modeling of the semanticspace of the personality was carried out in thesecontrast groups. Experimental psychosemantics wasused as the methodological basis of the research. Themethod of personal semantic differential, the processingof which with the help of factor analysis made possibleto build models of the semantic space of the personalityof an acquaintance was used as the basicmethod for obtaining empirical data. Results. Comparativeanalysis has shown that the semantic spaceof the personality for active web-users is simpler intwo parameters: firstly, in the number of componentsof personal categories, and secondly, in the internalstructure of knowledge about the personalitypresented in the categories. Conclusions. The dataobtained reveal that adult web-users do not enhancetheir knowledge about the personality as comparedwith those who prefer traditional reading. The differencesidentified can be explained by the specificsof the word and the media image as units of informationcoding. Probably, the word is a stronger signsystem and a medium of propositional information,as compared with the media image that is a mediumof iconic information.
Keywords: categories of consciousness, semantic differential, factor analysis, cognitive complexity